Analysis of the Level of Community Satisfaction with the Implementation of the Telemedicine Technology Health Service Application (Mobile JKN) in Sanggrahan Village - Dinda Nur Wijayanti; Asti Nurhayati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Telemedicine is a long-distance health service carried out by health professionals using information and communication technology, and this is also expected to include the exchange of information for diagnosis, treatment, prevention of injury and research as well as evaluation of education. Research objective: is to determine the analysis of the level of community satisfaction with the implementation of the Telemedicine technology health service application (Mobile JKN) in Sanggrahan Village. The specific objective of this research is to find out: To determine the percentage of community satisfaction and dissatisfaction with the implementation of the telemedicine technology health service application ( Mobile JKN) in Sanggrahan Village. To find out the percentage of good or bad implementation of the Telemedicine technology health service application (Mobile JKN) in Sanggrahan Village. Method: This research is quantitative research with a survey approach. This research aims to collect numerical data to measure an analysis of the level of community satisfaction with the implementation of the Telemedicine technology health service application (Mobile JKN) in Sanggrahan Village. Results: Based on data analysis and discussion, the results of the research can be stated. It can be seen from the values ​​presented, the researcher found that good service quality will provide satisfaction for users. Conclusion: An overview of the level of community satisfaction in Sanggrahan Village is high for 50 respondents (100% ).The description of the implementation of the Mobile JKN application in Sanggrahan Village is mostly high with 40 respondents (80%). There is a relationship between community satisfaction with the implementation of the telemedicine technology health service application (Mobile JKN) in Sanggrahan Village, with a p-value of 0.000 (<0.05 ).